Satisfaction and protection of individual mobile telecommunications consumers: Need for regulation? - Covadonga Gijón Tascón; Teresa Garín Mu\~noz; Teodosio Pérez Amaral (International Telecommunications Society (ITS), 2012)
Mobile telecommunications markets have been studied primarily from the perspectives of mobile telecom operators, market organization and regulators. However, there have been few studies from the perspective of the private consumer, which is the object of this research. This paper is part of an ongoing project on the protection of individual mobile consumers. The main research questions of the project are whether, and to what extent, individual consumers of mobile telecommunications are satisfied or subject to dubious practices by mobile operators, possibly due to market failures, and whether improved regulation can increase the efficiency of the industry and the welfare of telecommunications consumers. The specific research question of this paper is how much customer satisfaction there is among private individual consumers of mobile telecommunications in Spain and what factors may be associated with this. Specifically, we formulate, estimate and interpret relationships between different aspects of satisfaction and its determinants. Some novelties of this paper are a new focus on individual consumers and the use of new data which convey high quality statistical information. We use cross-section data on 4953 individual consumers. We specify econometric models and estimate them using different techniques. Our data allow us to discriminate by operators, regions of residence (Autonomous Regions and provinces), gender, age and educational level, among others. Our results indicate that customers are less satisfied with the larger carriers like Telefónica and Vodafone, and more satisfied with smaller and newer operators. We measure the importance of each of the items of satisfaction to the overall satisfaction. We also estimate individual equations for each of the items of satisfaction and measure the importance of each of its determinants. Finally, we analyze the effects of the different types of complaints on each of the items of satisfaction.
Keywords: C21; D12; L52; L96; 330; Consumer satisfaction; consumer protection; mobile telecommunications; individual private consumers; survey data; cross section; econometric models